Specific chlamydial inclusion membrane proteins associate with active Src family kinases in microdomains that interact with the host microtubule network - Mital, Jeffrey (2010)
Chlamydiae are gram-negative obligate intracellular bacteria that cause diseases with significant medical and economic impact. Chlamydia trachomatis replicates within a vacuole termed an inclusion, which is extensively modified by the insertion of a number of bacterial effector proteins known as inclusion membrane proteins (Incs). Once modified, the inclusion is trafficked in a dynein-dependent manner to the microtubule organizing center (MTOC), where it associates with host centrosomes. Here we describe a novel structure on the inclusion membrane comprised of both host and bacterial proteins. Members of the Src family of kinases are recruited to the chlamydial inclusion in an active form. These kinases display a distinct, localized punctate microdomain-like staining pattern on the inclusion membrane that colocalizes with four chlamydial inclusion membrane proteins (Incs) and is enriched in cholesterol. Biochemical studies show that at least two of these Incs stably interact with one another. Furthermore, host centrosomes associate with these microdomain proteins in C. trachomatis-infected cells and in uninfected cells exogenously expressing one of the chlamydial effectors. Together, the data suggest that a specific structure on the C. trachomatis inclusion membrane may be responsible for the known interactions of chlamydiae with the microtubule network and resultant effects on centrosome stability.